Nilai Sosial Dalam Novel Kubah Karya Ahmad Tohari: Kajian Sosiologi Sastra Serta Implementasinya Sebagai Bahan Ajar Sastra Di SMA N 1 Jatinom - Yanto, Yanto; , Drs. Zainal Arifin, M.Hum (2016)
The purpose of this study to describe 1) The structure of the novel builders of the Dome by Ahmad Tohari 2) The social values of the Dome of the novel by Ahmad Tohari, 3) Implementation of the Dome of the novel by Ahmad Tohari to study of literature in SMA N 1 Jatinom. This study used a qualitative descriptive approach. Source data from the Dome of the novel. Data in the form of words, sentences and paragraphs. Data collection techniques using literature techniques, see and record. Mechanical validity of the data using triangulation data. Data were analyzed using the methods of dialectics. The analysis showed that the structure of the novel builders of the Dome consists of themes good activity in life. Chronology of the groove mix. Figures that Karman, Marni, Tini, Haji Bakir, Triman, Margo, and Gigi Baja. Viewpoint that people use all three main actors. Message contained in the novel should be able to understand and give forgiveness to someone who has realized kesalahanya and those who have realized kesalahnya must be able to prove that he has changed, go back to the beaten path. The social value of the novel consists of Love (affection) composed of devotion, mutual help, family, loyalty, and caring. Responsibility (responsibility) consists of the value of a sense of belonging, discipline and empathy. Life Harmony (harmony of life) consists of the values of justice, tolerance, cooperation, and democracy.